IMPLEMENTATION OF THE KLANGEN COFFEE & ROASTERY MARKETING PUBLIC RELATIONS STRATEGY IN FORMING A POSITIVE IMAGE IN THE EYES OF THE PUBLIC: IMPLEMENTASI STRATEGI PUBLIC RELATIONS MARKETING KLANGEN COFFEE & ROASTERY DALAM MEMBENTUK CITRA POSITIF DI MATA PUBLIK - Pramasti Adiyatni Pranoto; Niken Ayu Salsabila Putri (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
TThe development of coffee shop business trends in Indonesia has increased over the last few years. Even though Indonesia was hit by the COVID-19 pandemic, it did not discourage businessmen in the industry. In fact, several businessmen started their businesses during the pandemic, including Klangen Coffee & Roastery. As a businessman who operated during the pandemic, Klangen Coffee & Roastery employed a Marketing Public Relations strategy to survive in the competitive coffee shop business and create a positive image in the public eye. This study uses Harold Lasswell's Propaganda theory and a focus method that includes five elements of communication: source, message, channel or media, receiver, and effect. The research aims to understand Klangen Coffee & Roastery's Marketing Public Relations strategy in shaping a positive image in the public eye. The interpretive qualitative research methodology involves conducting in-depth interviews and observations. The study's results suggest that Klangen Coffee & Roastery's Marketing Public Relations strategy has been successful but not yet fully maximized. Researchers also see that the use of content can have a fairly good impact or effect when delivered through Instagram and TikTok.